Respuesta :
(gof)(x)=g(f(x))
(gof)(4)=g(f(4))
g(f(4))
find f(4) first
f(4)=4(4)-7=16-7=9
g(f(4))=g(9)=9+3=12
(gof)(4)=12
the domain is the usable numbers
(fog)(x)
look at each
f(x)=2/x
x can be any number except 0
find what x in g(x) results in 0
0=|x|-1
add 1
1=|x|
1=x
-1=x
domain of (fog)(x) is all real numbers except for x=-1 and 1
(gof)(4)=g(f(4))
g(f(4))
find f(4) first
f(4)=4(4)-7=16-7=9
g(f(4))=g(9)=9+3=12
(gof)(4)=12
the domain is the usable numbers
(fog)(x)
look at each
f(x)=2/x
x can be any number except 0
find what x in g(x) results in 0
0=|x|-1
add 1
1=|x|
1=x
-1=x
domain of (fog)(x) is all real numbers except for x=-1 and 1